Knowledge and Preventive Practice of Dengue Fever among Students studying in MMAMC Biratnagar - Kumari, Rana Namta; Pokhrel, Alisha (Journal of Biratnagar Nursing Campus, 2023)
Introduction: Dengue is a vector-borne viral disease that has rapidly spread in many countries in recent years. Dengue Shock Syndrome have become major public health concern which clearly evident to give attention to follow the healthy behaviors and attitude for its prevention and control. The objective of the study is to assess the knowledge and preventive practice of dengue fever among students studying in MMAMC, Biratnagar. Methods: A descriptive cross-sectional research was conducted in Mahendra Morang Adarsh Multiple Campus in September 2018, among 271 students using non probability purposive sampling technique. Self-administered questionnaire was used for data collection and analyzed by descriptive and inferential statistics. Result: Out of 271 students 55.7% were male and 44.3% were female. The overall mean and standard deviation of the age was 20.65±1.53 years. The study revealed that the respondents had inadequate knowledge (85.6%) and inadequate preventive practice (64.2%) of dengue fever. There was no significant association between level of knowledge and level of preventive practice on dengue fever with p <0.05. Conclusion: This study concluded that majority of the respondents had inadequate knowledge regarding dengue fever and more than half of the respondents had a inadequate preventive practice. Despite the rapid expansion of dengue virus in Nepal, the knowledge and preventive practice of respondents on dengue fever was very low. Educational intervention and awareness program on dengue fever are recommended for its prevention.